Pengaruh Latar Belakang Pendidikan Terhadap Kinerja Pegawai di Kantor Desa Nagori Naga Dolok - Hengki Mangiring Parulian Simarmata; Poltak Pardamean Simarmata; Doris Yolanda Saragih (Yayasan Literasi Sains Indonesia, 2023)
Reliable Human Resources (HR) is the primary key in the Organization. This study aims to determine the influence of educational background on team member performance at the Nagori Naga Dolok Village Office, Simalungun Regency. The research uses qualitative and descriptive approaches to obtain the data by distributing questionnaires. The sample used by all Village Office employees was 33 people. Data was collected and then tested for validity, reliability test, and normality test. The analysis technique used is simple linear regression analysis using SPSS software. The hypothesis test results are proven where the significance value is below 0.05, meaning that educational background has a significant positive effect on team member performance at the Nagori Naga Dolok Village office, Simalungun Regency. The magnitude of the influence of variable X on variable Y, with a linear regression test of 0.642, means that the extent of the impact of variable X on variable Y is 64.2%. The remaining 35.8% is influenced by other factors not examined in this study.